2006
DOI: 10.1016/j.ydbio.2006.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the retinal determination gene dachshund in the embryonic head and developing eye of Drosophila

Abstract: The retinal determination gene dachshund is distantly related to the family of Ski/Sno proto-oncogenes and influences the development of a wide range of tissues including the embryonic head, optic lobes, brain, central nervous system as well as the post-embryonic leg, wing, genital and eye-antennal discs. We were interested in the regulatory mechanisms that control the dynamic expression pattern of dachshund and in this report we set out to ascertain how the transcription of dachshund is modulated in the embry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 73 publications
4
21
0
Order By: Relevance
“…Also, larval Otdac RNAi resulted in smaller compound eyes with rough ommatidial surfaces, including ommatidial misarrangements and partial fusion of ommatidia, phenotypes similar to those observed in Drosophila dac mutants (Fig. 3A) (37). These phenotypes were observed in 81% of pupae (n ϭ 25/31) and 89% (n ϭ 16/18) of adults generated.…”
Section: Resultssupporting
confidence: 71%
“…Also, larval Otdac RNAi resulted in smaller compound eyes with rough ommatidial surfaces, including ommatidial misarrangements and partial fusion of ommatidia, phenotypes similar to those observed in Drosophila dac mutants (Fig. 3A) (37). These phenotypes were observed in 81% of pupae (n ϭ 25/31) and 89% (n ϭ 16/18) of adults generated.…”
Section: Resultssupporting
confidence: 71%
“…Genetic epistasis analyses position dac as the most downstream among the known components of the RDGN (Figure 1) (9,10). Retinal tissue with mutations in ey, so, or eya has markedly reduced levels of dac expression (9,10,42,63), suggesting that Ey, So, and Eya are primary regulators of dac expression; however, persistence of a low level of dac expression implies additional factors may modulate www.annualreviews.org • Eya Phosphotyrosine PhosphatasesBMP: Bone Morphogenetic Protein its expression. Identification and characterization of two eye-specific enhancer elements within the dac genomic locus support this idea (64).…”
Section: Transcriptional Hierarchies Within the Rdgnmentioning
confidence: 99%
“…Some studies indicate that Vitamin C increases circulating immunoglobulin (Ig) levels in humans [17]. Vitamin C provide important protection for plasma lipid and lipid membranes and can neutralize phagocyte-derived oxidants released extracellular, thereby preventing oxidant mediated tissue damage [10]. This study showed that Vitamin C concentration showed no significant difference between the male and female levels.…”
Section: Resultsmentioning
confidence: 79%
“…Micronutrients deficiency is common in ageing, pregnancy and ill health [14]. These deficiencies may contribute to an increased risk of parasitic infection, and oxidative stress which affect the production of blood cells and haemoglobin and the entire immune level [10]. The study showed that there is synergism between α-tocopherol, β-carotene and ascorbic acid.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation